Implementasi Model Pembelajaran Group Investigation Untuk Hasil Kreativitas Dalam Menginvestigasi Dan Kemampuan Presentasi Siswa - Taufik Hidayat; Sofyan Hasanudin Nur; Anna Fitri Hindriana (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2018)
This study is entitled the aims of study to analyze the implementation of the Group Investigation learning model, analyze differences in the creativity of student investigation between the control class and the experimental class, analyze the ability of student presentations between the control class and the experimental class and to determine the response of student’s to the learning. The research method used was the Quasy Experiment with the Nonequivalent Control Group research design. The population in this study were all students of X-MIA class 1 Jamblang Senior High School 2017/2018 Academic Year. The sample in the study were students of class X-MIA 3 as an experimental class using the Group Investigation learning model and X-MIA 6 class as a control class with Discovery Learning learning model. The results showed (1) the implementation of Group Investigation model learning was carried out very well starting from the introduction to closing activities with an average percentage of 83.7%. (2) there are differences in student’s investigative creativity ability between the experimental class and the control class, in the creativity experiment class they investigate it better than the control class. (3) there are differences in presentation skills between the experimental class and the control class, in the experimental class student's presentation skills are better than the control class. (4) 53.3% of students gave a strong response, while the remaining 46.7% of students gave a very strong response, so that the average student gave a strong response to the Group Investigation learning modeKeywords: Investigative Creativity Ability; Presentation Ability; Group Investigation Learning